Effect of heat treatment on microstructure and mechanical properties of laser deposited TA15/Ti2AlNb gradient composite structures. (August 2021) - He, Bo; Wu, Dan; Pan, Jielin; Yang, Guang
Abstract: TA15/Ti2 AlNb gradient composite structures without obvious metallurgical defects were successfully fabricated by synchronous powder-feeding laser deposition manufacturing (LDM), followed by different heat treatments. Results showed that the laser-deposited three-layer TA15/Ti2 AlNb gradient composite can effectively reduce the microstructure difference between adjacent composition layers and the transition is gentle. The sizes of α and α2 phases in the microstructure of each gradient layer in annealed state are larger than those in as-deposited state and solution aged state. The annealed TA15/Ti2 AlNb gradient composite has the best tensile strength of 909.27 MPa and elongation of 6.73%. The fracture of as-deposited sample has more characteristics of cleavage fracture, while the fractures of annealed and solution aged tensile samples have more ductile feature. And there are more dimples in annealed fracture, presenting better toughness, which is consistent with the tensile test results. As the proportion of Ti2 AlNb increases, the corresponding microhardness increases before decreases. Highlights: Gradient TA15/Ti2 AlNb composite without metallurgical defects was successfully prepared by LDM. The size of α/α2 phase in each gradient layer after annealing is relatively larger. Annealing can effectively improve the comprehensive properties of LDMed gradient TA15/Ti2 AlNb.